2019
DOI: 10.1017/s003329171900028x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic functional network connectivity in unmedicated bipolar and major depressive disorders based on the triple-network model

Abstract: BackgroundPrevious studies have analyzed brain functional connectivity to reveal the neural physiopathology of bipolar disorder (BD) and major depressive disorder (MDD) based on the triple-network model [involving the salience network, default mode network (DMN), and central executive network (CEN)]. However, most studies assumed that the brain intrinsic fluctuations throughout the entire scan are static. Thus, we aimed to reveal the dynamic functional network connectivity (dFNC) in the triple networks of BD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 70 publications
5
58
0
Order By: Relevance
“…Detailed neurophysiological correlates of resting-state activity are currently the object of speculation and only specific analysis techniques (i.e. dynamic functional connectivity) can account for the complex dynamics in the interactions between brain regions as suggested by some studies (Brady et al, 2017;Wang et al, 2020). Furthermore, since the BOLD contrast reflects hemodynamic/metabolic processes in the brain, the interpretation of rs-fMRI findings in terms of the underlying neuronal activity is not straightforward and would require the integration of electrophysiological information (Maggioni et al, 2016).…”
mentioning
confidence: 99%
“…Detailed neurophysiological correlates of resting-state activity are currently the object of speculation and only specific analysis techniques (i.e. dynamic functional connectivity) can account for the complex dynamics in the interactions between brain regions as suggested by some studies (Brady et al, 2017;Wang et al, 2020). Furthermore, since the BOLD contrast reflects hemodynamic/metabolic processes in the brain, the interpretation of rs-fMRI findings in terms of the underlying neuronal activity is not straightforward and would require the integration of electrophysiological information (Maggioni et al, 2016).…”
mentioning
confidence: 99%
“…Kucyi et al suggested dFC within DMN is positively associated with emotion control (55). Abnormal intra-and internetwork connectivity variability are linked with mood disorders (56). Inter-network connectivity dynamics also contribute to cognitive flexibility (57), which is a key element of executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as two related but distinct diseases, major depression and BD patients may present disparate brain-function temporal dynamics. However, there is no uniform conclusion about the common or specific alterations of brain-function temporal dynamics (56,59). Further studies included BD I and II type and major depression to explore the differentiating signatures of brainfunction temporal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Zhi et al (2018) used the sliding-window algorithm to identify three types of node damage which were related to the severity of depressive symptoms and cognitive ability. Wang et al (2019) found decreased DFC variability between the anterior DMN and the right CEN compared with controls (Wang et al, 2019). It is noteworthy that initial attempts have been made to validate that the accuracy of a machine learning-based diagnosis system could be largely improved by using DFC metrics, instead of traditional SFC measures .…”
Section: Introductionmentioning
confidence: 98%